Propofol anesthesia decreases the incidence of new-onset postoperative atrial fibrillation compared to desflurane in patients undergoing video-assisted thoracoscopic surgery: A retrospective single-center study. - Karin Tajima; Kentaro Yamakawa; Yuki Kuwabara; Chika Miyazaki; Hiroshi Sunaga; Shoichi Uezono (PLoS ONE, 2023)
Background Postoperative atrial fibrillation (POAF) increases postoperative morbidity, mortality, and length of hospital stay. Propofol is reported to modulate atrial electrophysiology and the cardiac autonomic nervous system. Therefore, we retrospectively examined whether propofol suppresses POAF in patients undergoing video-assisted thoracoscopic surgery (VATS) compared to desflurane. Methods We retrospectively recruited adult patients who underwent VATS during the period from January 2011 to May 2018 in an academic university hospital. Between continuous propofol and desflurane administration during anesthetic maintenance, we investigated the incidence of new-onset POAF (within 48 hours after surgery) before and after propensity score matching. Results Of the 482 patients, 344 received propofol, and 138 received desflurane during anesthetic maintenance. The incidence of POAF in the propofol group was less than that in the desflurane group (4 [1.2%] vs. 8 patients [5.8%], odds ratio [OR]; 0.161, 95% confidence interval (CI), 0.040-0.653, p = 0.011) in the present study population. After adjustment for propensity score matching (n = 254, n = 127 each group), the incidence of POAF was still less in propofol group than desflurane group (1 [0.8%] vs. 8 patients [6.3%], OR; 0.068, 95% CI: 0.007-0.626, p = 0.018). Conclusions These retrospective data suggest propofol anesthesia significantly inhibits POAF compared to desflurane anesthesia in patients undergoing VATS. Further prospective studies are needed to elucidate the mechanism of propofol on the inhibition of POAF.